Quantitative determination of immunoglobulin IgM and apolipoprotein A1 in schizophrenia population - Heidari Keshel, Saeed; Sadough, Nahid; Omidinia, Skandar; Rahmanzadeh, Saeid (Archives of Advances in Biosciences, 2013)
Schizophrenia is a mental disorder painful with prevalence of about 1% in the world. Nowadays, there is no experimental test aiding the accurate diagnosis of schizophrenic patients but recently quantitative determination of some serum proteins led to many investigations on the roles of these in neuropsychiatric.In the present study, our aim is to quantitative determination ApoA1 and IgM between 134 schizophrenic patients and 127 healthy control persons. Schizophrenia patients were selected from the Tehran Razi hospital. The age (p=0.53) and sex distributions of schizophrenic patients were similar to those of control persons. We measured ApoA1 and IgM levels by immunoturbidimetry method. P<0.05 was considered significant. ApoA1 showed a significant decrease in serum (p=0.00) and IgM to be significantly increased (p=0.00).Furthermore, female patients showed an increase IgM more than males. These results for ApoA1 and IgM support other reports. Decrease ApoaA1 confirmed the relationship of lipid metabolism in schizophrenia patients, also increase IgM evaluate the impact of treatment. This report can help to identify disease markers and treatment such as immunoglobulin therapy or regulate lipid metabolism. It can be imagined that immunoglobulin therapy more effective in the female patients than male and need to expa